A costloss analysis to evaluate the value of weather estimates as inputs to a disease risk model - Kim, K.S.; Beresford, R.M.; Henshall, W.R. (New Zealand Plant Protection, 2008)
To assess the value of weather estimates the expenses including the cost of spray application and the losses incurred because of a disease were analysed using disease risk simulations In this case study the risk of botrytis bunch rot was simulated using weather estimates as inputs to a disease risk model Those estimates were obtained using spatial interpolation and nearest neighbour methods Possible cost was calculated based on 2 by 2 matrices under the assumption that fungicide spray decisions were made using the disease risk model with estimated weather data The expenses associated with each combination of decisions on spray application and outcome were compared between weather estimates and measurements